Lessons from the field an assessment of SIBAT experiences on community-based microhydro power systems. (Sibol ng Agham at Teknolohiya, 2005)
Sibol ng Agham at Teknolohiya (SIBAT) facilitated the establishment of community-based renewable energy system (CBRES) since 1994. SIBAT in their quest for further development to improve RE has conducted this study on 3 regions namely: CAR or Cordillera Administrative Region, Samar in Eastern Visayas and the Bicol Region. Aside from the recommendations, three (3) key areas of improvement were found. These includes the : improvement of the organizational model, improvement of income generation through productive energy use and improvement of financing of the investment needs. This book also contains case studies of community-based micro hydro power projects.